2017
DOI: 10.5301/ejo.5000924
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4 Techniques for Limbal-Conjunctival Autograft Fixation in Primary Pterygium Surgery

Abstract: In primary nasal pterygium surgery, limbal-conjunctival autograft fixation using cautery is the technique with the lowest postoperative discomfort rate and without a statistically significant increase in recurrence rate when compared to conventional suture and fibrin glue techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…It has been reported already that cautery autograft fixation has reduced postoperative discomfort compared with autograft fixation with sutures, fibrin glue and autologous fibrin glue. 20 Studies including autografting with electrocautery pen compared with suture autografting have showed that thermal welding can be safe and fast alternative, with less postoperative discomfort. 12 Idea of hybrid technique for joined suturing and cauterisation has been presented for large pterygia, and further usage of bipolar cautery has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported already that cautery autograft fixation has reduced postoperative discomfort compared with autograft fixation with sutures, fibrin glue and autologous fibrin glue. 20 Studies including autografting with electrocautery pen compared with suture autografting have showed that thermal welding can be safe and fast alternative, with less postoperative discomfort. 12 Idea of hybrid technique for joined suturing and cauterisation has been presented for large pterygia, and further usage of bipolar cautery has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Mejia et al 10 compared four limbal-conjunctival autograft fixation techniques – conventional suture, commercial fibrin glue, autologous fibrin glue, and cautery – in primary pterygium surgery. The authors found that limbal-conjunctival autograft fixation with cautery was the technique with the lowest postoperative discomfort rate, as well as the one not having a statistically significant increase in recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…8 A less expensive and alternative option to fibrin glue involves conjunctival autograft fixation induced by hemostasis of the patient’s own serum and electrocauterization. 810…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common surgical techniques include simple pterygium excision, conjunctival autograft transplantation, pterygium transposition, pterygium excision combined with amniotic membrane transplantation, limbal-conjunctival autograft transplantation, and adjunctive therapies such as use of mitomycin C, anti-VEGFs, or antibrotics. [8][9][10][11]. Pterygium transposition can change the direction of pterygium growth, but it affects the facial beauty of patients.…”
Section: Introductionmentioning
confidence: 99%